General Laws, Memorials and Resolutions of the Territory of Dakota 128, § 454 (4th Sess. 1864-65) - (:unkn) unknown (My University, 1864)
"Every person who carries upon his person, whether concealed or not, or uses or attempts to use against another, any instrument or weapon of the kind usually known as slung shot or of any similar kind is guilty of felony."
Keywords: CARRY